Black Is King, Beyoncé Knowles-Carter, Kwasi Fordjour, Emmanuel Adjei, Blitz Bazawule, Ibra Ake, Jenn Nkiru, Jake Nava, Pierre Debusschere and Dkayl Rimmasch (dirs) (2020). Issue 1 (1st April 2021) - Ealey, Jordan
Review of: Black Is King, Beyoncé Knowles-Carter, Kwasi Fordjour, Emmanuel Adjei, Blitz Bazawule, Ibra Ake, Jenn Nkiru, Jake Nava, Pierre Debusschere and Dkayl Rimmasch (dirs) (2020)USA: Disney+